Online Courses in the Context of Inclusive Education - N. V. Grechushkina (Высшее образование в России)
One of the areas of the theory and practice in the modern pedagogy is providing conditions and guarantees in socialization and equal access to education for all members of the society including persons with special educational needs. Persons with special educational needs (SEN) are the subjects of inclusion who have atypical features in their development or living conditions. These atypical features may be the cause of uncomplete realization of the right to education. Online courses may be viewed as a resource of inclusive education since they have great potential for educational process organization and implementation for the learners with special educational needs – subjects of inclusion. The paper discusses the possibility and potential benefits of using online courses for different categories of SEN learners. In particular, online courses can serve as instruments of additional pedagogical support in designing student’s individual educational trajectory as well as instruments of socialization.